2022
DOI: 10.21833/ijaas.2022.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the differences in positive-negative psychological factors influencing the life satisfaction and depression of college students by gender and family economic level

Abstract: This study identifies the factors affecting life satisfaction and depression of Korean college students and analyzes the differences between gender and family economic level in positive (self-esteem, ego-resilience, self-identity, life satisfaction) and negative emotions (attention deficit, aggression, depression, social withdrawal). The data from the 7th year of the Korean Children and Youth Panel Survey (KCYPS) conducted by the Korea Youth Policy Research Institute (KCYPS) with a total of 2,351 university st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In contrast, college freshmen from economically disadvantaged families may face higher economic stress during their growth process, which can increase their risk for mental health problems such as depression, anxiety, and interpersonal sensitivity. 72 , 73 Moreover, students from families with lower economic status typically receive less family support, and their parents may experience behavioral or emotional problems due to their disadvantaged economic position, leading to increased conflict between family members. 74 Some parents may have low income and need to work long hours, leaving them with insufficient attention, caring, and understanding for their children, resulting in increased psychosocial distress among the children.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, college freshmen from economically disadvantaged families may face higher economic stress during their growth process, which can increase their risk for mental health problems such as depression, anxiety, and interpersonal sensitivity. 72 , 73 Moreover, students from families with lower economic status typically receive less family support, and their parents may experience behavioral or emotional problems due to their disadvantaged economic position, leading to increased conflict between family members. 74 Some parents may have low income and need to work long hours, leaving them with insufficient attention, caring, and understanding for their children, resulting in increased psychosocial distress among the children.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that family as well as self-esteem were positive contributors to life satisfaction in over 3,310 students (Lábiscsák-Erdélyi et al, 2022). It is important to highlight the study of Jun and Jung (2022) who analyzed 1,220 college students and found that those who had higher family and significant positive emotions manifested higher life satisfaction and self-esteem. The report by Moksnes et al (2022) highlights significant positive associations between selfesteem and life satisfaction in 1,816 students, emphasizing the need to promote self-esteem, belonging, and social integration to support students' life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Jun and Jung [29] identify the factors affecting life satisfaction of Korean college students, using the data from the Korea Children's Youth Panel Survey (KCYPS) conducted by the Korea Youth Policy Institute. The KCYPS was conducted in 2010 to identify the growth and developmental patterns of children and adolescents.…”
Section: Research On Life Satisfaction Of College Studentsmentioning
confidence: 99%